Attitudes of schoolchildren towards physical education and its relation to the level of physical activity (Revista horizonte, 2022)
The purpose of this study was to determine the attitudes of students towards physical education, and the level of physical activity according to gender; also, to establish the relation between the attitudes of students towards physical education and the level of physical activity. 320 high school students were surveyed (65% boys, 35 % girls, age M=15.49, SD=1.24). The Attitudes Towards Physical Education Questionnaire (CAEF) and The Physical Activity Questionnaire for Adolescents (PAQ-A) have been used. The results indicate that the students have positive attitudes towards Physical Education, being higher in boys (M=2.79,SD=0.24) than in girls(M=2.64, SD= 0.26), with significant differences between the two genders. In total, the students could be classified as physically inactive (M=2.49,SD=0.78). The boys are more active (M=2.72,SD=0.79) than the girls (M=2.07,SD=0.58). This difference is statistically significant. A significant relation between the attitudes towards physical education and the level of physical activity (r=0.42) has also been established. The results of this study indicate that, considering the relationship between the attitudes and levels of physical activity and the differences between the two genders, it is important to consider the development of strategies to increase positive attitudes towards physical education, especially in girls.